Análise, projeto e desenvolvimento de um sistema UPS on-line com elevado fator de potência utilizando célula a combustível como fonte auxiliar de energia - Maciel, Renato Santiago (2019)
This work presents the development of an experimental on-line UPS system using a fuel cell as an auxiliary power supply, as well as the development and implementation of a digital DSP (Digital Signal Processor) control technique that uses the method of average current for the front-end Boost converter, imposing a sinusoidal current in the AC network in order to respect the harmonic distortion limits of currents imposed by the standard IEC 61000-3-2 and obtain a high power factor and a bipolar open-loop control for the Full-bridge inverter that is able to guarantee the continuity and quality of the power supply for essential loads. Detailed the operation principle of the proposed UPS system, qualitative and quantitative analysis, design specifications, simulation and experimental results obtained from the implementation of a 500W prototype are presented.